2015
DOI: 10.1016/j.physbeh.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The glucagon-like peptide 1 (GLP-1) receptor agonist exendin-4 reduces cocaine self-administration in mice

Abstract: Glucagon-like peptide 1 (GLP-1) analogues are used for the treatment of type 2 diabetes. The ability of the GLP-1 system to decrease food intake in rodents has been well described and parallels results from clinical trials. GLP-1 receptors are expressed in the brain, including within the ventral tegmental area (VTA) and the nucleus accumbens (NAc). Dopaminergic neurons in the VTA project to the NAc, and these neurons play a pivotal role in the rewarding effects of drugs of abuse. Based on the anatomical distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
97
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 30 publications
(47 reference statements)
7
97
0
Order By: Relevance
“…The ability of the GLP-1 system to modulate dopamine signaling, likely underlying reward-driven behavioral alterations, is supported by studies employing microdialysis. Using this technique, which samples fluctuations in extracellular dopamine over minutes, studies have shown suppression of cocaine-induced increases in NAc dopamine concentration by Exendin-4 [35,39]. Our data suggest that this suppression is limited to the NAc core (Figures 3 and 4) and that terminal mechanisms for shaping extracellular dopamine concentration (e.g.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The ability of the GLP-1 system to modulate dopamine signaling, likely underlying reward-driven behavioral alterations, is supported by studies employing microdialysis. Using this technique, which samples fluctuations in extracellular dopamine over minutes, studies have shown suppression of cocaine-induced increases in NAc dopamine concentration by Exendin-4 [35,39]. Our data suggest that this suppression is limited to the NAc core (Figures 3 and 4) and that terminal mechanisms for shaping extracellular dopamine concentration (e.g.…”
Section: Discussionmentioning
confidence: 56%
“…Previous work demonstrating suppression of dopamine by Exendin-4 used systemic injection [35,39] which would target both peripheral and central GLP-1Rs, as Exendin-4 does cross the blood brain barrier [90]. While our data suggest a central site of action, the central population of GLP-1Rs that are targeted to exert effects on dopamine signaling remains unknown.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Furthermore, the presence of or even the expectancy of cocaine depresses leptin concentrations, while leptin administration inhibits cocaine-induced seeking behavior and reward (You et al, 2016). The administration of the GLP-1 analog exendin-4 to rodents reduces the rewarding effects of cocaine, cocaine self-administration and cocaine-induced CPP (Egecioglu et al, 2013; Graham et al, 2013; Reddy et al, 2016; Schmidt et al, 2016; Sørensen et al, 2015). In contrast, insulin enhances the function of cocaine-sensitive dopamine and norepinephrine transporters in the rat NAc by acting at the presynaptic level (Schoffelmeer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%